Prolonged and Inappropriate Central Line Utilization in Nursing Homes (NH) Related to Broad Spectrum Antibiotics. (4th October 2017) - Gohil, Shruti K; Alsharif, Mohamad; Nourollahi, Shereen; Tam, Steven; Rashid, Syma; Chang, Justin; Bahadori, Bardia; Singh, Raveena D; Huang, Susan S
Abstract: Background: Continuation of intravenous therapy via peripherally inserted central catheters (PICCs) after hospitalization is a common reason for NH care. Little is known about timely removal of central lines after planned treatment is complete. Methods: In this observational prospective cohort study of residents with PICCs at 6 NHs between September 4, 2015 and December 31, 2016, we evaluated reason for admission, antibiotic use and planned duration, PICC line indication and dwell time, and oral intake status. Results: Among 420 residents with PICCs, the most common indication for PICC line use was antibiotics (77%), followed by 13% of patients who had no documented indication. Infection was cited as the primary reason for NH admission with a PICC in 79% (333) of residents; among these, sepsis (27%), skin/soft-tissue infection (24%), and osteomyelitis 19%) were the most common reasons. Among 324 patients on antibiotics, vancomycin (33%), piperacillin/tazobactam (21%), and carbapenem (12%) were most common and 77% of all antibiotics were broad spectrum. Average planned antibiotic therapy duration was 21 days (range 0–91). Mean dwell time for PICC lines was 31 days (range 1–300). Among 203 PICC lines where antibiotic stop dates were available, 77% remained in place >2 days despite completion of antibiotics; 54% remained >7 days and 36% remained more than 2 weeks without clear indication for intravenous access. Average duration of lines remaining in place despite discontinuation of antibiotics was 18 days (range 0–320). Overall, among lines remaining in place post-completion of antibiotics, the average extended duration was 18 days (range 0–320). NPO status was noted in 12% of residents. Conclusion: We found that the vast majority of antibiotic use in NHs were broad spectrum agents. Additionally, inappropriately prolonged PICC presence post-antibiotic discontinuation occurred in three-quarters of those with PICC lines, often for several weeks. Strategies to ensure timely removal of central lines, such as daily documentation of line necessity, are urgently needed in the NH setting. Opportunities also exist for antibiotic stewardship interventions. Disclosures: S. K. Gohil, Sage Products: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Xttrium Laboratories: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Clorox: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; S. Tam, Sage Products: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; 3M: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Xttrium Laboratories: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Clorox: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; J. Chang, Sage Products: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Xttrium Laboratories: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Clorox: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product 3M: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; R. D. Singh, Sage Products: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; 3M: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Xttrium Laboratories: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Clorox: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; S. S. Huang, Sage Products: Receipt of contributed product, Conducting studies in which participating healthcare facilities are receiving contributed product (no contribution in submitted abstract), Participating healthcare facilities in my studies received contributed product; Xttrium Laboratories: Receipt of contributed product, Conducting studies in which participating healthcare facilities are receiving contributed product (no contribution in submitted abstract), Participating healthcare facilities in my studies received contributed product; Clorox: Receipt of contributed product, Conducting studies in which participating healthcare facilities are receiving contributed product (no contribution in submitted abstract), Participating healthcare facilities in my studies received contributed product; 3M: Receipt of contributed product, Conducting studies in which participating healthcare facilities are receiving contributed product (no contribution in submitted abstract), Participating healthcare facilities in my studies received contributed product; Molnlycke: Receipt of contributed product, Conducting studies in which participating healthcare facilities are receiving contributed product (no contribution in submitted abstract), Participating healthcare facilities in my studies received contributed product